Preemptive analgesia using selective cyclooxygenase-2 inhibitors alleviates postoperative pain in patients undergoing total knee arthroplasty: A protocol for PRISMA guided meta-analysis of randomized controlled trials. Issue 7 (19th February 2021) - Wang, Congcong; Fu, Hongjuan; Wang, Jun; Huang, Fujun; Cao, Xuejun
Abstract: Background: The postoperative pain associated with total knee arthroplasty (TKA) is severe for most patients. The analgesic efficacy and safety of preoperative use of selective cyclooxygenase-2 (COX-2) inhibitors for patients undergoing TKA are unclear. Objectives: We conducted a systematic review and meta-analysis to assess whether the use of selective COX-2 inhibitors before TKA decreases the postoperative pain intensity. Methods: Data sources: The PubMed, Embase, EBSCO, Web of Science, and Cochrane Controlled Register of Trials databases from inception to January 2020. Study eligibility criteria: All randomized controlled trials (RCTs) in which the intervention treatment was preoperative selective COX-2 vs placebo in patients undergoing TKA and that had at least one of the quantitative outcomes mentioned in the following section of this paper were included. Letters, review articles, case reports, editorials, animal experimental studies, and retrospective studies were excluded. Interventions: All RCTs in which the intervention treatment was preoperative selective COX-2 vs placebo in patients undergoing TKA. Study appraisal and synthesis methods: The quality of the RCTs was quantified using the Newcastle–Ottawa quality assessment scale. RevMan 5.3 software was used for the meta-analysis. Results: Six RCTs that had enrolled a total of 574 patients were included in the meta-analysis. The visual analog scale pain score at rest was significantly different between the experimental group and control group at 24 hours ( P  < .05) and 72 hours ( P  < .05) postoperatively. The experimental group exhibited a significant visual analog scale pain score during flexion at 24 hours postoperatively ( P  < .05), and it was not different at 72 hours postoperatively ( P  = .08). There was a significant difference in opioid consumption ( P  < .05), but there was no difference in the operation time ( P  = .24) or postoperative nausea/vomiting ( P  = .64) between the groups. Conclusion: The efficacy of preoperative administration of selective COX-2 inhibitors to reduce postoperative pain and opioid consumption after TKA is validated. Systematic review registration number: INPLASY202090101